Measurement of R&D efficiency in NT and BT fields using DEA:a case in Korea - Park, Hanseok; Choi, Hoo-Gon (International Journal of Engineering and Technology, 2013)
Since the Korean government has increased the R&D budget for both BT and NT areas, it needs to measure R&D efficiency and to manage the budget. The purpose of this study is to measure the efficiency of more than 2,000 BT and NT related projects supported by four basic research programs with the BCC-O model of the DEA method. Two input and five output variables are considered to determine the efficiency. The average efficiencies of both fields are low (0.3532 in the BT and 0.4677 in the NT) and the DEA projection results show that all output measures should be improved as much as 240% to 423% to be at efficiency 1. Also, correlation analysis is used to determine which variables strongly affect the efficiency in the BT and NT areas. This study could facilitate the development of better processes for project selection and many types of evaluation, provided the quantitative method such as the DEA could become widely acceptable for researchers.